Profile of Cervical Cancer Patients Undergoing Chemotherapy at Abdoel Wahab Sjahranie Hospital Samarinda for the 2020-2021 Period - Rahma, Rosyida Muthia; Sawitri, Endang; Achmad, Andika Adi Saputra; Ngo, Novia Fransiska; Yuniati, Yuniati (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Cervical cancer was a malignant disease of the cervix caused by infection with HPV (Human Papilloma Virus) which was spread through skin contact, mainly due to sexual activity. There were many risk factors that cause HPV infection. Generally, cervical cancer was only discovered at an advanced stage. The treatment for cervical cancer recurrent or metastases was chemotherapy. This study aimed to determined the profile of cervical cancer patients undergoing chemotherapy at the Abdoel Wahab Sjahranie Hospital Samarinda for the 2020-2021 period. The research design was descriptive observational with a cross-sectional approach by took affordable samples. The samples obtained as many as 95 samples. The results showed that the low-risk age (<35 years) were 6.3% and the high-risk age (≥ 35 years) 93.7%, with the mean age was 48.49 years; low education level were 33.7%, moderate 54.7%, and high 11.6%; patients who were nullipara 3.2%, primipara 13.7%, multipara 68.4%, and grande multipara 14.7%; single agent chemotherapy regimen 86.3% and combined agent 13.7%. The conclusion that most cervical cancer patients who undergoing chemotherapy were at high-risk age, moderate education level, multipara, and chemotherapy regimen single agent.